FUNCTIONAL MOVEMENT SCREENING IN THE PHYSICAL FITNESS TEST IN HIGH SCHOOL ADOLESCENTS - Li,Qindong (2022)
ABSTRACT Introduction: Functional Movement Screening is a qualitative triage of human movement based on a classification and scoring system which includes seven tests to evaluate basic movement patterns where muscle limitations or asymmetries are identified. Its scale has 21 points, with 14 being the limit of normality. Adolescence is critical to improving athletic ability, and the validity of applying this screening technique to discover potential injuries is questioned. Objective: To verify the validity of functional movement screening on the early detection and correction of dysfunctional movements to implement physical fitness in adolescents. Methods: Functional movement screening was performed on students from a school. According to the screening requirements, functional movement examinations were performed before (October 2017) and after (December 2017) intervention with individual demand functional training. Results: After functional training, students’ physical fitness increased from 13.00±0.44 to 14.77±0.28 points (p<0.05). Conclusion: The results of functional movement assessment can analyze the physical problems of adolescents in universities and colleges. Targeted functional training can effectively improve the physical fitness of adolescents in schools and colleges. Evidence Level II; Therapeutic Studies – Investigating the results.